2019
DOI: 10.3390/molecules24183207
|View full text |Cite
|
Sign up to set email alerts
|

Platycodigenin as Potential Drug Candidate for Alzheimer’s Disease via Modulating Microglial Polarization and Neurite Regeneration

Abstract: Neuroinflammatory microenvironment, regulating neurite regrowth and neuronal survival, plays a critical role in Alzheimer’s disease (AD). During neuroinflammation, microglia are activated, inducing the release of inflammatory or anti-inflammatory factors depending on their polarization into classical M1 microglia or alternative M2 phenotype. Therefore, optimizing brain microenvironment by small molecule-targeted microglia polarization and promoting neurite regeneration might be a potential therapeutic strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…As inhibiting M1 microglia alone is not enough, promoting M2 microglia activation simultaneously might also be required for treating neurodegenerative diseases ( Yang et al, 2019 ). Promoting microglia polarization shift from M1 to M2 phenotype may be a more prospective strategy in the therapy of neurodegenerative diseases such as AD, PD, ALS, and MS ( Wen et al, 2017 ; Zhang B. et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As inhibiting M1 microglia alone is not enough, promoting M2 microglia activation simultaneously might also be required for treating neurodegenerative diseases ( Yang et al, 2019 ). Promoting microglia polarization shift from M1 to M2 phenotype may be a more prospective strategy in the therapy of neurodegenerative diseases such as AD, PD, ALS, and MS ( Wen et al, 2017 ; Zhang B. et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that LPS significantly increased the production of NO at concentrations ranging from 10 to 1000 ng/mL without cell toxicity. 15 We used LPS at a concentration of 100 ng/mL for the following investigations. Different doses of HED (0.01-25 μM) were used for the 24-hour treatment of either BV2 microglia or LPS-treated microglia.…”
Section: Resultsmentioning
confidence: 99%
“…BV2 microglia cells were obtained from the Institute of Biochemistry and Cell Biology (Shanghai, China) and cultured in DMEM/high medium (Hyclone, Logan, Utah, USA) supplemented with 10% fetal bovine serum (FBS, Gibco, Grand Island, New York, USA) and 1% penicillin-streptomycin (Gibco, USA) at 37 °C in a 5% CO2/95% air incubator [54].…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
“…Alexa Fluor 594-conjugated goat antimouse IgG (1:200, ab150116, Abcam, Cambridge, England) was used as secondary antibody. DAPI (Biomol, Hamburg, Germany) was used for counterstaining [54]. Fluorescence images were captured by a fluorescence microscope system (OLYMPUS IX73, Olympus, Japan).…”
Section: Immunofluorescencementioning
confidence: 99%